Mireya Jaimes-Freyre, Modernismo y 98 a través de Ricardo Jaimes Freyre. Gredos, Madrid, 1969; 206 pp. - Meyer-Minnemann, Klaus (El Colegio de México, 1972)
Se reseñó el libro: Modernismo y 98 a través de Ricardo Jaimes Freyre.